Phytoremediation for nutrient removal in an environmentally friendly floating cage system: a field experiment - Astuti, Lismining Pujiyani; Warsa, Andri; Sentosa, Agus Arifin; Tjahjo, Didik Wahju Hendro; Sembiring, Tarzan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Aquaculture is one of the efforts to optimize the utilization of water bodies. Aquaculture using floating net cages is detrimental to water, namely causing pollution from uneaten feed and fish excretion. Water quality would be degraded due to eutrophication, oxygen depletion, and uncontrolled growth of algae and aquatic plants. High concentrations of nitrogen and phosphorus mainly trigger water quality degradation and eutrophication. To reduce the negative impact of aquaculture activities in floating net cages in reservoir/lake waters, an environmentally friendly cage technology that is low waste is needed. The technology offered is a loop bio-phytoremediation system equipped with floating net cages, a water management system with recirculation, and plants. The floating net cage used is a double net where the upper net consists of two nets and a bottom net. The upper net is used for rearing carp fish, and the bottom net for tilapia. The plants used as phytoremediation agents were water spinach and vetiver grass. Moreover, the physical filter used for processed water before recirculating to the waterbody in the FNC consists of sand, palm fiber, and limestone layers. The results showed that the effectiveness of nutrient removal on water spinach hydroponic (HRT=15 h), vetiver grass wetland (HRT=36 h), and physical filters (HRT=2,4 h) in reducing nitrate was 83%, 86%, and 67%, respectively; maximal reduction of the organic matter reached 94%, 96%, and 96%, respectively; as well as the highest reduction in total phosphorus was 78%, 89%, and 82%, respectively.